Chiropractic management of a patient with symptoms of attention-deficit/hyperactivity disorder - Muir, Jeffrey M. (Elsevier, 2012)
OBJECTIVE: The purpose of this study is to report a case of a child with attention-deficit/hyperactivity disorder (ADHD) who was treated with chiropractic care. CLINICAL FEATURES: Parents of a 5-year-old boy with diagnosed ADHD brought him for chiropractic care to address his subjective signs (acting out, ability to follow instructions, and poor home and school performance), which also included waking at night due to asthmatic symptoms and low self-esteem. Palpation revealed hypertonicity and trigger points in the paraspinal muscles at the thoracolumbar region with local pain. A preliminary diagnosis included cervical and thoracolumbar facet joint irritation with concurrent muscle hypertonicity. INTERVENTION AND OUTCOMES: Treatment including spinal manipulative therapy, soft tissue therapy, and stretching was provided. Treatment began on a thrice-weekly basis and declined to twice weekly over the course of approximately 12 weeks. After 1 year of treatment, subjective improvements were noted in episodes of acting out, ability to follow instructions, and general home and school performance. CONCLUSIONS: The patient improved over 1 year in which he received chiropractic care, including manual treatments such as spinal manipulative therapy and soft tissue therapies. This suggests that there may be a role for doctors of chiropractic in the management of patients with ADHD.